A study on the morbidity pattern in adolescent school girls - Sinha, Shivani; Gupta, Pratibha; Sachan, Beena; Kumar, Sanjay; Kumari, Seema (International Journal Of Community Medicine And Public Health, 2017)
Background: The World Health Organization (WHO) has defined adolescence as the age group of 10-19 years. According to World Health Organisation, adolescents constitute about one fifth of the world population, and in India they constitute about 21% of the total population. Adolescent girls are the worst sufferers of various forms of malnutrition because of their increased nutritional needs and low social power. If their nutritional needs are not met, they are likely to give birth to undernourished children, thus transmitting under nutrition to future generation. Objective was to study the various socio-demographic factors affecting the nutritional status in adolescent girls. Methods: A school based cross-sectional study was carried out in Lucknow district. Adolescent girls of age groups 10-19 years were included in the study. Data was collected, compiled and tabulated using Microsoft Excel and analysed using SPSS 17.0 version for calculation of percentages. Results: Rural background, low socioeconomic status, illiteracy, birth rate and order, income and number of members in a family have shown to be significant determinants of morbidity pattern in the adolescent girls. Conclusions: Among the various morbidities eye problem was seen in maximum no of adolescent girls. Eye problem was present in 31% of adolescent girls followed by respiratory (12.8%) and ear (11.5%) disease. Skin disease was present in 3.1% of adolescent girls, which was more in rural girls than in urban girls, may be due to better hygienic practice in urban school girls.